Public expenditure policy in Bolivia: Growth and welfare - Carlos Gustavo Machicado; Paul Estrada; Ximena Flores (Institute for Advanced Development Studies (INESAD), 2010)
It has been widely documented that fiscal policy can promote economic growth, when it is based on an efficient provision of pubic capital. But little work has been done, in Bolivia, in relation to the macroeconomic and sectoral impacts of increasing public investment in infrastructure. This paper develops a Dynamic Stochastic General Equilibrium (DSGE) model for a small open economy with five sectors: Non-tradable or services, importable or manufacturing, hydrocarbons, mining and agriculture. The model is parameterized and solved for the Bolivian economy and several interesting scenarios are simulated by changing government expenditures, taxes, country risk, Total Factor Productivity, effectiveness of public capital and terms of trade. This analysis is relevant for the Bolivian economy, because the government is using fiscal policy as one of its main tool to attack poverty and aims to put public investment as the foremost instruments to promote growth and welfare.
Keywords: E62; H54; O41; 330; Fiscal Policy; Infrastructure; Multisector Growth Model; Finanzpolitik; Infrastrukturinvestition; Dynamisches Gleichgewicht; Kleines-offenes-Land; Mehr-Sektoren-Modell; Bolivien